2022
DOI: 10.1021/acsami.2c03695
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Longevity of a Novel Gallium Liquid Metal/Hydroxyapatite Composite Coating Fabricated by Plasma Spray

Abstract: Hydroxyapatite (HAp)-coated metallic implants are known for their excellent bioactivity and osteoconductivity. However, infections associated with the microstructure of the HAp coatings may lead to implant failures as well as increased morbidity and mortality. This work addresses the concerns about infections by developing novel composite coatings of HAp and gallium liquid metal (GaLM) using atmospheric plasma spray (APS) as the coating technique. Five weight percent Ga was mixed into a commercially supplied H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 61 publications
(110 reference statements)
1
13
0
Order By: Relevance
“…The CA for HAP coating was measured as 96°, which shows the comparatively hydrophobic surface of the material. The hydrophobic surface of HAP coatings with CA in the same range was also presented by Pham et al , 42 whose results showed a CA of 107° for the HAP coating. Moreover, the addition of reinforcements provided a hydrophilic surface for the HAP–CNT, HAP–GrO and HAP–hBN coatings (Fig.…”
Section: Resultssupporting
confidence: 77%
“…The CA for HAP coating was measured as 96°, which shows the comparatively hydrophobic surface of the material. The hydrophobic surface of HAP coatings with CA in the same range was also presented by Pham et al , 42 whose results showed a CA of 107° for the HAP coating. Moreover, the addition of reinforcements provided a hydrophilic surface for the HAP–CNT, HAP–GrO and HAP–hBN coatings (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Liquid metal core–shell composites refer to a kind of material that consists of a functional shell and liquid metal core. [ 83–85 ] In many cases, such shells exhibit enhancements in liquid metal functionality. [ 84,86,87 ] For example, Guo et al.…”
Section: Liquid Metal Compositesmentioning
confidence: 99%
“…Liquid metal core-shell composites refer to a kind of material that consists of a functional shell and liquid metal core. [83][84][85] In many cases, such shells exhibit enhancements in liquid metal functionality. [84,86,87] For example, Guo et al [88] found that in situ reduced gold-coated liquid metal nanodroplets exhibited stronger photothermal conversion effects.…”
Section: Liquid Metal Core-shell Compositesmentioning
confidence: 99%
“…The additional coating methods increase the surface hydrophilicity by taking advantage of the hydrophilic biomaterials. Biomaterials used for implant coatings are broadly classified into ceramics (Díaz-Cuenca et al 2022;Li et al 2022), polymers (Tao et al 2020;Tallet et al 2021), and metallic systems (Pham et al 2022;Yan et al 2022). However, the problems of cytotoxicity, shedding of coatings, and a lack of mechanical properties still exist.…”
Section: Introductionmentioning
confidence: 99%